Pseudomonas fluorescens Pf-5 genome-wide mutant screen for resistance to the antimicrobial peptide alfalfa snakin-1 - Ayub, Nicolás Daniel; Fox, Ana Romina; Garcia, Araceli Nora; Mozzicafreddo, Matteo; Cuccioloni, Massimiliano; Angeletti, Mauro; Pagano, Elba Maria; Soto, Gabriela Cynthia (Oxford University Press, 2021)
Snakin-1, a peptide produced by higher plants, has broad-spectrum antibiotic activity, inhibiting organisms ranging from Bacteria to Eukaryotes. However, the mode of action against target organisms is poorly understood. As a first step to elucidate the mechanism, we screened a mutation library of Pseudomonas fluorescens Pf-5 in LB and agar medium supplemented with alfalfa snakin-1 (MsSN1). We identified three biofilm formation-related Pseudomonas mutants that showed increased resistance to MsSN1. Genetic, physiological and bioinformatics analysis validated the results of the mutant screens, indicating that bacterial adhesion protein lapA is probably the target of MsSN1. Collectively, these findings suggest that snakin-1 acts on microbial adhesion properties.